KOSAKATA DALAM â€œMUAR SANGATâ€ (TRADISI MENGAMBIL MADU) PADA MASYARAKAT DAYAK JALAI KETAPANG - Wahyudi, Firli; Amir, Amriani; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract Muar is one of the richest traditions of the Dayak Jalai Ketapang community which is the cultural asset of the community and is the legacy of its forefathers. This research as an effort to preserve and inventory vocabulary in the tradition of muar sangat by describing the meaning of lexical and cultural meaning. This linguistic-related study focuses on the vocabulary of the highly developed (tradition of taking honey) to the Dayak Jalai Ketapang people. This research used descriptive method, qualitative research form. The data in this research consisted of tool vocabulary, processes, time, mantra, name of plant and animal, and folklore starting from pre-implementation, implementation and post-implementation.This study succeeded in compiling 128 vocabulary consisting of 33 tools vocabulary, 21 processes vocabulary, 8 times vocabulary, 24 plants vocabulary, 4 animal vocabulary, and 22 vocabulary in mantra, and 16 vocabulary on folklore. All the data obtained from interviews conducted by researchers while in the village Biku Sarana, District Jelai Hulu, Ketapang District. The data in the form of the vocabulary as a whole has a cultural meaning but in the analysis conducted there is data that is not found the lexical meaning.Keywords: Muar sangat, Dayak Jalai Ketapang, lexical meaning, cultural meaning.